Exploring the relationship between letter recognition and handwriting in early literacy development. (September 2019) - Reutzel, Pamela; Mohr, Kathleen AJ; Jones, Cindy D
Previous research has demonstrated correlation between letter-naming and letter-writing fluency, and a relationship between letter-naming fluency and successful reading development. Awareness of critical features of letters has received less attention as a part of handwriting development, but it is theorized to also play a role in letter-writing fluency. This study sought to delineate possible components of letter-writing fluency using four related tasks with kindergarten students. Results confirm the correlation between letter-naming and letter-writing fluency and indicate that recognition and manipulation of critical letter features correlate with letter-writing fluency. Findings suggest that awareness of critical features could be a part of early literacy instruction.